2020
DOI: 10.1055/s-0039-1700853
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Gestational Weight Gain in Each Trimester and Pregnancy Outcomes in Twin Pregnancies

Abstract: Objective Adequate maternal weight gain in twin pregnancies is associated with improved outcomes such as increased fetal growth and decreased incidence of preterm birth. However, it remains unclear when gestational weight gain has the greatest influence on pregnancy outcomes. Our objective was to identify at which time in a twin pregnancy does inadequate maternal weight gain have the greatest association with adverse pregnancy outcomes. Study Design This is a retrospective cohort study of women with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(34 citation statements)
references
References 20 publications
(24 reference statements)
1
31
2
Order By: Relevance
“…Wen et al reported that in dichorionic twins, weight gain in early pregnancy was found to be associated with birth weight (28). Lilly et al reported that weight gain in the second and rst trimesters of pregnancy is associated with fetal growth, whereas weight gain after 24 weeks is associated with preterm labor (20). However, the above studies are different from our research in that these were studies on normal weight twin pregnancies.…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…Wen et al reported that in dichorionic twins, weight gain in early pregnancy was found to be associated with birth weight (28). Lilly et al reported that weight gain in the second and rst trimesters of pregnancy is associated with fetal growth, whereas weight gain after 24 weeks is associated with preterm labor (20). However, the above studies are different from our research in that these were studies on normal weight twin pregnancies.…”
Section: Discussioncontrasting
confidence: 82%
“…Furthermore, the rate of preterm labor and short cervical length during pregnancy was high in the underweight group; thus, the possibility of emergency delivery was higher. According to Lilly et al, if weight gain by underweight mothers during pregnancy reached the recommended value for normal BMI mothers, the frequency of preterm labor and pregnancyrelated complications did not increase (20). We found that underweight women had relatively smaller weight gains, which is a study of Asians who are relatively small compared to Westerners who have been mainly studied so far, so it is thought that there is a difference in these results.…”
Section: Discussionmentioning
confidence: 45%
“…10 Eight studies accounted for BMI group through stratification, 10,20,[22][23][24][29][30][31] six through adjustment 12,21,25,28,33,34 and one used both stratification and adjustment. Three studies accounted for BMI group by restriction to the normal weight category 27,32,35 and one study by restriction to the overweight and obese categories. 26 Thirteen studies used mean weekly GWG to account for the impact of duration of pregnancy on GWG, 12,20,22,[24][25][26][27][28][29][30][31]34,35 two studies achieved this by restricting to term births, 21,33 one by using GWG z-score for gestational week at birth, 10 one used a gestational-age specific cutoff of Luke et al, 36 and two did not account for this variable and were therefore excluded from the meta-analysis.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Three studies accounted for BMI group by restriction to the normal weight category 27,32,35 and one study by restriction to the overweight and obese categories. 26 Thirteen studies used mean weekly GWG to account for the impact of duration of pregnancy on GWG, 12,20,22,[24][25][26][27][28][29][30][31]34,35 two studies achieved this by restricting to term births, 21,33 one by using GWG z-score for gestational week at birth, 10 one used a gestational-age specific cutoff of Luke et al, 36 and two did not account for this variable and were therefore excluded from the meta-analysis. 19,32 Six studies adjusted for chorionicity 21,25,29,31,34,35 and three adjusted for artificial reproductive therapies.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Twin pregnancy consists presence of fetal co-existence inside the uterine cavity. Usually, represents fertilization of two eggs from two sperms (dizygotic twins), or fertilization of one egg, separation of the gamete and formation of two embryos (Monozygotic Twins) [1]. All conducted studies from current bibliography estimate incidence of twin pregnancy about 2% of all other pregnancies [2].…”
Section: Introductionmentioning
confidence: 99%